European Union Foreign Policy and the Global Climate Regime - Schunz, Simon (Peter Lang International Academic Publishers, 2014)
This book engages in a longitudinal analysis of the EU's participation in and impact on the global climate change regime, providing a thought-provoking audit of the potential and limits of the EU's influence as a foreign policy player in a major domain of global affairs.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Political Science / History & Theory; Political science; Electronic books